The single moving dipole source for electrocardiography inverse problem in 3D human model - Dang, Thanh Trung (H. : ĐHQGHN, 2017)
Computing electrical source in the heart from potentials on the body surface is an illposed problem of electocardiogram (ECG). It is so diffrcult to get an exact solution of this problem. To solve this ECG inverse problerg a numerical analysis is used for forward problem with a specifrc .source model. Then, the solutions of ECG inverse problem is reached by using an iterative tecbnique, Newton or downhill simple:g to find the best source whose potentials best match to the observed potentials in a least s{uare sense. Such methods, however, often converge to a local minimum and their results are affected by initial panmeters. In this paper, soruce is considered as a moving single equivalent dipole and genetic algorithrn, an efficient and robust optimization method, is proposed to estimate parameters of source. In additiorl some irr4rrovements are introduced to enhance performance of conventional genetic algorithnr A 3D volume conductor model of human body is constructed base on an anatomic atlas for numerical test. A corrparison between our approach and one using downhill simplex method is implemented. The results show that our approach is stable and may provide a good scheme for solving the ECG inverse problem.